Diferensiasi Karsinoma Kolorektal di Rumah Sakit Umum Daerah (RSUD) Ciawi, Kabupaten Bogor Periode 2021 - 2023 - Sjaiful Bachri; Fernando Nathaniel; Velika Elaine Kangnata; Dean Ascha Wijaya; Sung Chian; Belinda Junitia; Yohanes Firmansyah (Pusat Riset dan Inovasi Nasional, 2023)
Colorectal carcinoma, a malignant neoplasm originating from the epithelial cells of the large intestine or rectum, poses a significant health problem worldwide. The estimated global incidence of colorectal cancer was 2.17 million cases in 2019. Meanwhile, in Indonesia, colorectal cancer ranks fifth among the most common cancer cases with a mortality rate of 9.5%. Demographic characteristics, including age, gender, ethnicity, and geographic location, have been extensively studied in relation to colorectal carcinoma. Understanding the patterns of differentiation and demographic characteristics associated with this disease is crucial for the diagnosis, treatment, and overall prognosis of patients. This study is a descriptive observational study that examines the demographic characteristics and differentiation of colorectal carcinoma patients. The study sample consists of a subset of the research population at Ciawi Regional General Hospital who underwent surgery from June 2021 to May 2023. A total of 21 respondents met the inclusion criteria, with a mean age of 54 years, and were predominantly female (57.1%). The results of this study indicate that poorly differentiated colorectal carcinoma generally occurs at a younger age compared to well and moderately differentiated cases. In terms of gender, females are more likely to experience colorectal carcinoma compared to males. Further research is needed to uncover the interactions between tumor biology, demographics, and clinical outcomes, with the ultimate goal of improving the prognosis and survival rates for individuals with colorectal carcinoma.